THE INFLUENCE OF THE USE OF AUDIO VISUAL MEDIA PROGRAM ON THE INCREASING OF ELEMENTARY SCHOOL STUDENTS CHARACTER BUILDING (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
Character deterioration that must be considered by a nation is a low sense of individual and citizen responsibility, Character is very important in a person's life, because character is one of the determinants of one's success. So, a strong and positive character needs to be well formed. Building the character of students as good citizens is very important to be done immediately, in the era of the digital era, many future generations of people who behave negatively such as saying dirty, lying, fighting, this indicates that the problem of student character has not been widely given in schools. This implies the need for action from schools to prevent acts of violence (bullying) in the school environments. Furthermore, this indicates the need for special attention to character education among students, especially regarding the improvement of the character building of elementary school students. This study aims to determine the effect of using audio visual media programs on improving the character building of elementary school students. The success of a program can be identified by looking at the effectiveness and efficiency of the program's learning process. This study also aims to determine changes in behavior and results through audiovisual media programs.